Glory O'Brien's history of the future - King, A. S. (Amy Sarig), 1970- (Little, Brown and Co., 2014)
"As her high school graduation draws near, Glory O'Brien begins having powerful and terrifying visions of the future as she struggles with her long-buried grief over her mother's suicide"--Provided by publisher.